Análisis de vulnerabilidad en el contexto del COVID-19 para el mercado municipal del cantón San Miguel provincia Bolívar - Shuishi Banshuy, Hilda María (2021)
The present study aims to carry out a vulnerability analysis in the context of COVID-19 to users and workers of the municipal market of the San Miguel canton, Bolívar province. For this, a quantitative, cross-sectional and exploratory approach was methodologically proposed as it is a relatively unknown problem. The population under study was made up of merchants and administrative workers who work in the municipal market of the canton of San Miguel. The necessary information was collected by means of two closed questionnaires addressed to the market traders and the administrators. With the information tabulated and analyzed, by means of descriptive statistics, it was possible to verify that biosecurity measures were not applied, aimed at generating barriers to contain the spread, within the municipal market facilities, being a risk for both users as for the workers. Likewise, it was determined that the population under study was composed mostly of people from vulnerable groups who are exposed to the virus, due to the lack of biosafety measures structured in predefined guidelines, which allow the authorities the mechanisms to its application, in order to properly manage sanitary measures in a timely manner. These insights led to the design of an easy-to-understand guide, to be used by merchants and market administrators, which is recommended to be disclosed and applied immediately, in order to promote safe spaces and reduce the risk of contagion by COVID-19 when using the facilities of the municipal market of SanMiguel. Key Words: Vulnerability, COVID-19, Biosecurity, Municipal Market